Improving skills and care standards in the support workforce for older people: a realist synthesis of workforce development interventions - Jo Rycroft-Malone; Christopher R Burton; Lynne Williams; Stephen Edwards; Denise Fisher; Beth Hall; Brendan McCormack; Sandra Nutley; Diane Seddon; Roger Williams (National Institute for Health Research, 2016)
Background: Support workers make up the majority of the workforce in health and social care services for older people. There is evidence to suggest that support workers are not deployed as effectively as possible, are often undervalued, and that there are gaps in understanding support worker roles across different care settings. In the context of a population that is growing older, having a skilled and knowledgeable workforce is an imperative. Workforce development includes the support required to equip those providing care to older people with the right skills, knowledge and behaviours to deliver safe and high-quality services. Objective: The review answered the question 'how can workforce development interventions improve the skills and the care standards of support workers within older people's health and social care services?'. Design: A realist synthesis was conducted. In realist synthesis, contingent relationships are expressed as context-mechanism-outcomes (CMOs), to show how particular contexts or conditions trigger mechanisms to generate outcomes. The review was conducted in four iterative stages over 18 months: (1) development of a theoretical framework and initial programme theory; (2) retrieval, review and synthesis of evidence relating to interventions designed to develop the support workforce, guided by the programme theories; (3) 'testing out' the synthesis findings to refine the programme theories and establish their practical relevance/potential for implementation; and (4) forming recommendations about how to improve current workforce development interventions to ensure high standards in the care of older people. Participants: Twelve stakeholders were involved in workshops to inform programme theory development, and 10 managers, directors for training/development and experienced support workers were interviewed in phase 4 of the study to evaluate the findings and inform knowledge mobilisation. Results: Eight CMO configurations emerged from the review process, which provide a programme theory about 'what works' in developing the older person's support workforce. The findings indicate that the design and delivery of workforce development should consider and include a number of starting points. These include personal factors about the support worker, the specific requirements of workforce development and the fit with broader organisational strategy and goals. Conclusions and recommendations: The review has resulted in an explanatory account of how the design and delivery of workforce development interventions work to improve the skills and care standards of support workers in older people's health and social care services. Implications for the practice of designing and delivering older person's support workforce development interventions are directly related to the eight CMO configuration of the programme theory. Our recommendations for future research relate both to aspects of research methods and to a number of research questions to further evaluate and explicate our programme theory. Limitations: We found that reports of studies evaluating workforce development interventions tended to lack detail about the interventions that were being evaluated. We found a lack of specificity in reports about what were the perceived and actual intended impacts from the workforce development initiatives being implemented and/or evaluated. Study registration: This study is registered as PROSPRERO CRD42013006283. Funding: The National Institute for Health Research Health Services and Delivery Research programme.